2014
DOI: 10.1063/1.4880736
|View full text |Cite
|
Sign up to set email alerts
|

Reversible control of magnetic domains in a Tb0.3Dy0.7Fe2/Pt/PbZr0.56Ti0.44O3 thin film heterostructure deposited on Pt/TiO2/SiO2/Si substrate

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They observed the orientation of the in-plane FE polarisation of the BaTiO 3 layer that depends on the position underneath the Fe dot using piezoresponse force microscopy, finding a significant change in the magnetic domain structure. Reversible electric-field-induced variation of the domain structure from an initial single-domain state to a transitional S-shape domain state was also observed in Ni nanobar/PZT using magnetic force microscopy [171] while reversible local manipulation of the magnetisation orientation was demonstrated in Tb 0.3 Dy 0.7 Fe 2 /Pt/PbZr 0.56 Ti 0.44 O 3 heterostructures on Pt/Si [172]. Furthermore, Buzzi et al clearly demonstrated using x-ray magnetic microscopy imaging that 90° magnetisation switching occurred in Ni dots/PMN-PT(1 1 0) heterostructures by controlling the orientation of FE polarisation of PMN-PT by applying an electric field [173].…”
Section: Magnetic Anisotropy and Magnetisation Switchingmentioning
confidence: 82%
“…They observed the orientation of the in-plane FE polarisation of the BaTiO 3 layer that depends on the position underneath the Fe dot using piezoresponse force microscopy, finding a significant change in the magnetic domain structure. Reversible electric-field-induced variation of the domain structure from an initial single-domain state to a transitional S-shape domain state was also observed in Ni nanobar/PZT using magnetic force microscopy [171] while reversible local manipulation of the magnetisation orientation was demonstrated in Tb 0.3 Dy 0.7 Fe 2 /Pt/PbZr 0.56 Ti 0.44 O 3 heterostructures on Pt/Si [172]. Furthermore, Buzzi et al clearly demonstrated using x-ray magnetic microscopy imaging that 90° magnetisation switching occurred in Ni dots/PMN-PT(1 1 0) heterostructures by controlling the orientation of FE polarisation of PMN-PT by applying an electric field [173].…”
Section: Magnetic Anisotropy and Magnetisation Switchingmentioning
confidence: 82%
“…Among various systems with magnetic domains, multi-ferroic=magnetoelectric materials=structures utilizing the above coupling have been recently demonstrated to exhibit small-scale magnetic stripe domain transformations. 15,19,20) However, these stripe domain transformations are not significant and thus are likely to have limited practical applicability. More recently, Hsu et al 21) reported a breakthrough in stripe domain transformations in a multiferroic Ni thin film= piezoelectric substrate.…”
mentioning
confidence: 99%
“…In that study, the Ni stripe domains were more significantly transformed by applied electric fields compared with previous studies. 15,19,20) However, after the applied electric field was turned off, the stripe domains were transformed back to their original configuration (i.e., the transformation was manifested only at the time of the electric field application). This result cannot achieve "permanent" data writing for practical data storage.…”
mentioning
confidence: 99%